NGABEO: THE STUDY OF TRANSMISSION METHOD OF DONGKARI AS A SINGING TECHNIQUE IN TEMBANG SUNDA CIANJURAN - Setiaji, Denis (Institut Seni Indoensia Surakarta, 2024)
The following research focused on explaining about the Ngabeo as a learning method in Tembang Sunda Cianjuran. This research used phenomenology as an approach as well as field activity and in-depth interviews with Penembang as a practitioner in Bandung City and collected data by virtual fieldwork. The research analyzed the ngabeo as the transmission process of knowledge, technique, and ornamentation as the operation of dongkari in the Tembang Sunda Cianjuran repertoire. Ngabeo as the traditional learning method in Tembang Sunda Cianjuran is the oral-aural transmission process used for inheritance the concept of sing in Tembang Sunda Cianjuran.